COMMUNICATION TRAINING METHODOLOGY IN PERCEPTION OF CONSUMER PSYCHOLOGY - Isamutdinovna, Salakhutdinova Musharraf; Ibodulla kizi , Safarova Maftuna (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the relevance of introducing the subject of consumer psychology into the program of psychological directions of higher educational institutions in the republic. It analyzes the psychology of the personality of the consumer, as well as the methodology of psychological training in communication with consumers.